The Effect of the Guided Inquiry Learning Model Assisted by Wordwall Media on Science Learning Interest and Achievement in Elementary Schools - Fahmi Hidayat; Nurlina; Agustan S (South Sulawesi Education Development (SSED), 2025)
The objectives of the study were to (1) analyze the influence of guided inquiry learning model assisted by Wordwall Media on students' interest in learning science at SDN 30 Sumpang Bita, (2) analyze the influence of guided inquiry learning model assisted by wordwall media on students' science learning outcomes, and (3) analyze the influence of guided inquiry learning model assisted by wordwall media on students' interest and science learning outcomes of grade IV SDN 30 Sumpang Bita. This study used aquantitative approach, with a non-equivalent control group design. The population in this study was all grade IV elementary school students in Region 2, Balocci District, Pangkep Regency, consisting of 10 schools totaling 113 students. The sampling technique used was random sampling. The sample in this study was SDN 30 Sumpang Bita selected as the experimental class with 20 students and SDN 6 Bulu-Bulu as the control class with 20 students. The data obtained were analyzed using normality and homogeneity tests, followed by hypothesis testing using the t-test in the MANOVA results. The results of the study showed that; (1) The guided inquiry learning model assisted by wordwall media has a significant effect on students' interest in learning science at SDN 30 Sumpang Bita. The results of the t-test analysis showed that the significance value (Sig = 0.000) was smaller than the set alpha value of 0.05 (0.000 <0.05). (2) The guided inquiry learning model assisted by wordwall media has a significant effect on students' science learning outcomes at SDN 30 Sumpang Bita. The results of the t-test analysis showed that the significance value (Sig=0.000) was smaller than the set alpha value of 0.05 (0.000 <0.05). (3) There is a significant influence between leaming interest and students' science learning outcomes applied with the guided inquiry learning model assisted by wordwall media at SDN 30 Sumpang Bita. The results of One-way Multivariate Analysis of Variance (One-way MANOVA) show that all statistics have very significant values with p-value (Sig.) = .000. This shows that the intercept significantly affects the dependent variable. It can be concluded that the guided inquiry learning model assisted by wordwall media has a significant effect on the interests and science learning outcomes of Grade IV students at SDN 30 Sumpang Bita.